Pengembangan Buku Cerita Bergambar Islami Berbasis Pendidikan Lingkungan Hidup untuk Pembelajaran Membaca di SD/MI - Nurul Hidayah; Rohmatillah Rohmatillah (AR-RIAYAH : Jurnal Pendidikan Dasar, 2021)
This research stems from the lack of variation in instructional media in teaching and learning activities, so it is necessary to develop a product in the form of a picture story book as a learning medium. The formulations of the problem are: (1) How is the development of learning media for Islamic picture book based on environmental education for reading learning in class III SD / MI, (2) Is it feasible to teach Islamic picture book learning media based on environmental education for learning to read in the classroom? III SD / MI, (3) How is the response of educators and students to the learning media of Islamic picture book based on environmental education for reading learning in class III SD / MI. This study aims to make students more interested and motivated in teaching and learning activities and understanding the importance of protecting the environment. This research is a research development or Research and Development with the ADDIE model which includes 5 steps, namely analysis, design, development, implementation evaluation. The product feasibility test was carried out by several validators, namely 2 media experts, 2 material experts, 2 linguists, 1 religious expert, 2 class III educators on grade III SD/MI students. The results showed that the learning media for Islamic picture book based on environmental education obtained an average value of the percentage of media experts who obtained a score of 80.25% with a very feasible category, material experts of 86.5% with a very decent category, linguists obtained a score 82.5% in the very feasible category, religious experts obtained a score of 87% in the very feasible category, the assessment of educators obtained an average percentage of 88.25% with the very feasible category and the response of students obtained an average percentage of 95.5% with a very decent category. This shows that the Islamic picture story book based on environmental education for reading learning in grade III SD / MI is very suitable for use as a learning medium.